Cover Feature: Identification of Broad‐Spectrum Dengue/Zika Virus Replication Inhibitors by Functionalization of Quinoline and 2, 6‐Diaminopurine Scaffolds (ChemMedChem 14/2018). (20th July 2018) - Kaptein, Suzanne J. F.; Vincetti, Paolo; Crespan, Emmanuele; Rivera, Jorge I. Armijos; Costantino, Gabriele; Maga, Giovanni; Neyts, Johan; Radi, Marco
Abstract : The Cover Feature shows how a single purine derivative inhibits the replication of multiple mosquito‐borne flaviviruses by targeting a conserved allosteric pocket on NS5 polymerase, which is needed to bind NS3 helicase/protease and generate the functional replication complex. These inexpensive non‐nucleoside broad‐spectrum antivirals inhibit the replication of Zika virus and all serotypes of dengue virus (DENV 1–4) in infected cells at low micromolar concentration, with no adverse effect on a panel of selected host kinases. More information can be found in the Communication by Marco Radi et al. onpage 1371 in Issue 14, 2018 (DOI:10.1002/cmdc.201800178 ).